Cryopreservation of germ cells as a conservation strategy for two valuable species in Mexico: Totoaba macdonaldi and Seriola lalandi - Mendoza-González, Leonardo D.; Suárez-López, Lucia; Paniagua-Chávez, Carmen G. (Frontiers in Marine Science, 2024)
The cryopreservation of cell lines such as primordial germ cells and germ cells is a promising strategy to conserve and reconstitute endangered or commercially important species in aquaculture. In Mexico, the northwest region is the center of the country’s most significant fishing and aquaculture production. However, most of the species used in capture fishing are overexploited. Despite this, protocols for the cryopreservation of germ cells are non-existent. Therefore, this work aimed to establish a protocol of isolation, identification, and cryopreservation of germ cells in two species, totoaba (Totoaba macdonaldi) and yellowtail amberjack (Seriola lalandi). Three concentrations of trypsin (0.25%, 0.3%, and 0.5%) were tested for gonadal dissociation. The 0.3% trypsin concentration was the best because it presented the most significant number of viable cells, with 14.35 × 105 for totoaba and 2.96 × 105 for yellowtail amberjack. The immunohistochemistry identification of germ cells in both species was positive for vasa, with 33.30% for totoaba and 34.20% for yellowtail amberjack. The cryoprotectant used was ethylene glycol (1.5 M or 2 M). The ideal temperature for the cryopreservation of gonadal tissue was different for each species, −1°C/min for totoaba and −5°C/min for yellowtail amberjack with 58.42% and 63.48% viable cells after thawing, respectively, with ethylene glycol 1.5 M being the best for both species. The non-controlled rate was the most effective technique to freeze the cell suspension, with 4.20 ± 1.09 × 105/mL viable cells for totoaba and 7.31 ± 2.25 × 105/mL for yellowtail amberjack. In conclusion, the results of the isolation, identification, and cryopreservation protocols for germ cells in totoaba and yellowtail amberjack obtained in this work are the first report for fish species from northwest Mexico, opening the door for the generation of cryobanking of germ cells. Finally, this work would help conserve endangered species and be an alternative to conserving species of commercial importance in aquaculture.